Characterizing sources and emissions of volatile organic compounds in a northern California residence using space- and time-resolved measurements - Liu, YingJun; Misztal, Pawel K.; Xiong, Jianyin; Tian, Yilin; Arata, Caleb; Weber, Robert J; Nazaroff, William W.; Goldstein, Allen H (Indoor Air, 2019)
Abstract We investigate source characteristics and emission dynamics of volatile organic compounds (VOCs) in a single-family house in California utilizing time- and space-resolved measurements. About 200 VOC signals, corresponding to more than 200 species, were measured during 8 weeks in summer and five in winter. Spatially resolved measurements, along with tracer data, reveal that VOCs in the living space were mainly emitted directly into that space, with minor contributions from the crawlspace, attic, or outdoors. Time-resolved measurements in the living space exhibited baseline levels far above outdoor levels for most VOCs; many compounds also displayed patterns of intermittent short-term enhancements (spikes) well above the indoor baseline. Compounds were categorized as ?high-baseline? or ?spike-dominated? based on indoor-to-outdoor concentration ratio and indoor mean-to-median ratio. Short-term spikes were associated with occupants and their activities, especially cooking. High-baseline compounds indicate continuous indoor emissions from building materials and furnishings. Indoor emission rates for high-baseline species, quantified with 2-hour resolution, exhibited strong temperature dependence and were affected by air-change rates. Decomposition of wooden building materials is suggested as a major source for acetic acid, formic acid, and methanol, which together accounted for \~75% of the total continuous indoor emissions of high-baseline species.
Keywords: air quality; cooking; material balance; occupancy; source apportionment; ventilation